Urethral Pain Syndrome: Treatment with Oxygen and Hyaluronic Acid - Vadalà, Maria; Veronesi, Ester; Garoia, Flavio (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: The aim of our clinical study has been to evaluate the efficacy of the association between high concentration oxygen and hyaluronic acid (HA) for the treatment of urethral pain syndrome (UPS). MATERIALS AND METHODS: Twenty women (45–65 years old) with suspected UPS diagnosis appealing to our Second Opinion Medical Consultation Network signed an informed consent form and were treated with oxygen/HA therapy treatment, 7 times a week, for a total of 5 weeks at the outpatient clinic (Clinic Ester Veronesi, Modena, Italy).The physicians of the Second Opinion Network followed up weekly from remote (WhatsApp, Skype) each treated patient as to state the effectiveness, tolerability, and side effects of the treatment. RESULTS: We observed significant reductions in number of urgency urinary incontinence (−25.37 vs. −12.01 mean value), nocturia episodes (−24.01 vs. −11.23 mean value), volume voided in each micturition (−127.79 vs. −98.20 mean value), and micturitions per 24 h (−44.01 vs. −20.12 mean value). Analyses of the pre- and post-treatment scores showed a statistically significant improvement in Vaginal assessment scale, pain urgency frequency, and patient perception of bladder condition scale scores (p < 0.0305, p < 0.0001, and p < 0.0001, respectively). No side effects associated with the treatment were reported by the patients. CONCLUSIONS: We can highlight that Caressflow® is effective and very well tolerated in UPS syndrome: The oxygen flow mixed with HA gives immediately a sense of freshness and urethro-bladder relaxation that lasts several hours. Further studies including larger sample sizes, placebo, and or challenge with other local and systemic treatments and different administration schedules versus longer follow-up are recommended.